Building a scientific attitude for Islamic elementary school students on Science Education learning based on science technology and society approach - Sulthon Sulthon (Prodi PGMI IAIN Salatiga, 2018)
The objectives of this study are to describe the practice of Science Education (IPA) learning at Islamic Elementary School (MI) and to develop the model based on Science Technology and Society (STS/STM) for building certain scientific attitudes. The qualitative approach was employed by searching data on the implementation of IPA learning through direct observation. The data are then analyzed descriptively. The results show that: 1) Science Education learning model based on Science Technology and Society gives students opportunity to conduct IPA process correctly and apply mutual relationship between IPA concept, technological progress, and life in society through five stages: invitation, exploration, explanation, consolidation of concepts or follow-up, and assessment; 2) Science Education learning model based on Science Technology and Society can build a scientific attitude and behavior of students to be sensitive, have a curiosity attitude, attitudes of proof, flexible attitude, critical attitude, caring attitude towards living creatures and environment, objective, honest, open, and cooperative. To strengthen and solidify the building process of this scientific attitude, it is conducted with a variety of relevant madrasa (school) activities through the habituation of activities beyond programmed science learning which include: building clean living habits in the madrasa environment; building park; performing reforestation; and fostering environmental sensitivity through community service programs in the village environment.